ANALISIS PENGARUH UPAH DAN JAMINAN SOSIAL TERHADAP KESEJAHTERAAN TENAGA KERJA (STUDI PADA PABRIK GULA (PG) KEBON AGUNG MALANG) - Batara, Surya Agung (Jurnal Ilmiah Mahasiswa FEB, 2017)
Labor welfare in the enterprise is a complex problem, the problem is increasing with dinormatifkannya wages and social security. Improved well-being living balance between the needs of materialism with spiritualism creating challenges and needs facing. Given the need for increasing the level of welfare of people faced with the increasing demands. This study aims to determine the relationship of wages and social security to workers in the PG kesejahtreraan. Kebon Agung Malang.The method used is quantitative, and data used are primary data obtained from the field through kuosioner of employees working on the production of sugar PG. Kebon Agung Malang, while the sampling technique using the entire population of permanent employees at the mill in PG. Kebon Agung Malang. The analytical tool used in this research is descriptive analysis (frequency distributions) and the tools used to analyze the data obtained using multiple linear regression. while for hypothesis test probability value test equipment that will measure the correlation probability value.The results showed that the level of wages and social security is directly proportional to the welfare of workers in the PG. Kebon Agung Malang. Thus if it occurs in an increase in wages and social security will be an increase in the welfare of workers.Keywords: Wages, Social Security, Welfare and Labor